2016
DOI: 10.4311/2015mb0108
|View full text |Cite
|
Sign up to set email alerts
|

Fungi isolated and quantified from bat guano and air in Harmanecká and Driny Caves (Slovakia)

Abstract: This study is the first mycological evaluation of bat guano and the air around it in Harmanecká and Driny Caves in Slovakia. These caves are the most important underground localities of bats in Slovakia. Samples were collected in July 2014 and cultivated for fungi. Harmanecká Cave had seven species of filamentous fungi and one yeast-like fungus isolated from bat guano, compared to six species of filamentous fungi in guano from Driny Cave. Air samples from Harmanecká Cave had twelve species of fungi, compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…3). The presence of these new species can be associated with anthropogenic factors, and the presence of bats in the Demänovská Cave of Liberty, because those factors can contribute to the qualitative and quantitative changes of fungal communities inhabiting underground areas (Griffin et al, 2014;Kokurewicz et al, 2016;Ogórek et al, 2016b).…”
Section: Resultsmentioning
confidence: 99%
“…3). The presence of these new species can be associated with anthropogenic factors, and the presence of bats in the Demänovská Cave of Liberty, because those factors can contribute to the qualitative and quantitative changes of fungal communities inhabiting underground areas (Griffin et al, 2014;Kokurewicz et al, 2016;Ogórek et al, 2016b).…”
Section: Resultsmentioning
confidence: 99%
“…(Nováková 2009; Bezerra et al 2012; Ogórek et al 2016a, b). The literature also reported that the active growth of this species was found on marten excrement in Domica Cave (Slovakia), but it was identified only by morphological features and without detailed characterization (Nováková 2005).…”
Section: Discussionmentioning
confidence: 99%
“…(Al-Doory & Rhoades, 1968;Carvajal, 1977a,b,c;Ashford ., 1999;Larcher ., 2003), sp (Lurie & Borok, 1955;Nováková, 2009;Martin-Sanchez ., 2014;) and , where the anthropogenic pressure remains high (Saiz-Jimenez, 2015). The species (Rippon, 1988;Moore-Landeckar, 1996) and (Fiorina , 2000;Ogorek ., 2016;Vanderwolf , 2013) isolated by us has also been reported earlier from some caves .…”
Section: Research Articlementioning
confidence: 99%